Foreign direct investment in post-reform India: Likely to work wonders for regional development? - Peter Nunnenkamp; Rudi Stracke (Kiel Institute for the World Economy (IfW), 2007)
We make use of a new and detailed database on FDI approvals since the early 1990s to address two major issues related to FDI and regional development in India in the post-reform period. First, we analyze the location choices of foreign investors. The evidence indicates that the concentration of FDI in a few relatively advanced regions may have prevented FDI effects from spreading across the Indian economy. Second, we evaluate whether the link between FDI and economic growth has become stronger in the aftermath of reforms. Various categories of FDI are indeed positively correlated with per-capita income growth across Indian states. However, it is only for the richer states that FDI appears to be associated with higher growth. FDI is thus likely to increase regional income disparity in India.
Keywords: O18; F23; O53; 330; Sub-categories of FDI; Location choice; Economic growth; Regional divergence; FDI approvals; Direktinvestition; Regionale Entwicklung; Standortwahl; Regionale Disparität; Schätzung; Indien